Musings on Patient Willingness to Pay - Dennis J. Baumgardner (Journal of Patient-Centered Research and Reviews, 2021)
The editor-in-chief of the Journal of Patient-Centered Research and Reviews introduces an original research article published within Volume 8, Issue 2, and comments on the relative willingness-to-pay values placed on various medical tests, treatments, and cures. How do we adequately educate patients on the risk of chronic disease and inspire them to embrace advisable lifestyle changes before there is a bigger bill to balk at?